(untitled) (Research, Society and Development, 2025)
It is responsibility of the State to ensure sanitary sewage. However, this is not the case, as data reveals that a large portion of the population does not have adequate access to it, with rural areas facing more gaps, primarily in public policies and management. In Pará de Minas/MG, this responsibility lies with the city, which outsources it to CAPAM (Companhia de Águas de Pará de Minas). Due to existing contracts, part of the rural area remains under the municipality’s management, leaving residents without access to services, demonstrating flaws and a need for solutions and changes. This article aims to discuss the factors contributing to this issue using elements of Organizational Engineering, with the goal of providing a more analytical view of the situation and suggesting potential improvements. Elements of strategic, organizational, and project management were used, along with analyses of the sanitation model described in the PMSB (Municipal Sanitation Plan), laws such as the Federal Basic Sanitation Policy, interviews with municipal government officials, company representatives, and residents of the Limas do Pará community, part of the municipality. These were compared with the provisions of the National Rural Sanitation Program (PNSR). Among the results are the lack of access to sanitation for the population, limited knowledge of technologies, and discrepancies regarding contracts and companies. Additionally, it was possible to understand the causes of the problems and identify solutions for each part of the issue, through the development of plans and alternative, sustainable technological solutions aimed at the population and managers.